التحكم الفعّال الأمثل بعدم اتزان الاحتراق في حارق نموذجي - محمود, حبيب (Latakia University Journal -Engineering Sciences Series, 2019)
إن تطبيق تقنية التحكم الفعال لإزالة حالات عدم الاستقرار أصبح حاجة ملحة في ظل الطلب المتزايد على منظومات احتراق عالية المردود وذات إصدارات منخفضة من الملوثات, ولكن الآلية المعقدة لحدوث عدم الاتزان ضمن أنظمة الاحتراق جعل من الصعب إيجاد نموذج رياضي دقيق يصف ديناميكية عدم الاتزان؛ لذلك فإن المحاولات الرامية لتصميم منظومة تحكم فعّال تعتمد بشكل كبير على المحاولة والخطأ. وهذا ما جعل الوصول إلى الحالة المثلى لتصميم المنظم أمراَ صعباَ. في هذا البحث، أُجريت دراسة تجريبية لاستقصاء ديناميكية الحارق غير المستقر، وتحديد تابع تحويله بالاعتماد على طريقة التوصيف. وبناءَ على تابع التحويل قمنا بتصميم المنظم ذي الأداء الأمثل باستخدام تقنية المنظم التربيعي الخطي LQR. وقد مكّننا هذا المنظم من ضبط الحارق وإزالة عدم الاستقرار خلال زمن مقداره 40 s في حين يحتاج المنظم المصمم بطريقة المحاولة والخطأ إلى حوالي 100 s, كما أن جهد التحكم المطلوب لعملية الضبط أقل بنسبة 75 %. Application of active control to element combustion instability has assumed greater significance with the ever increasing demand for high efficiency and low emission. Because of the complexity of instability occurring within combustion systems there are rare accurate models describing their dynamics. Therefore, attempts to design active control systems have largely been based on trial and error. As such, it is difficult to optimize these controllers. in this paper, an experimental study using identification techniques is conducted to investigate the dynamics of an unstable combustor and determine its transfer function. The optimal controller's design is based on the transfer function, using the linear quadratic regulator (LQR) technique. This controller has stabilized the combustor within the settling time of about 40s in comparison with 100s for the designed controller of the trial and error method. also, the control effort is less than 75%.